2016
DOI: 10.1017/s0033291716000027
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prevalence of non-suicidal self-injury in patients with eating disorders: a systematic review and meta-analysis

Abstract: Background. Against a backdrop of increasing research, clinical and taxonomic attention in non-suicidal self-injury (NSSI), evidence suggests a link between NSSI and eating disorders (ED). The frequency estimates of NSSI in ED vary widely. Little is known about the sources of this variation, and no meta-analysis has quantified the association between ED and NSSI.Method. Using random-effects meta-analyses, meta-regression analyses, and 1816-6466 unique participants with various ED, we estimated the weighted ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
134
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(151 citation statements)
references
References 56 publications
12
134
1
3
Order By: Relevance
“…Notably, similar ER difficulties have been postulated for EDs and NSSI behaviors; namely, both reveal difficulties in thinking, planning, or implementing adaptive coping strategies (Solano et al, 2005; Claes et al, 2010; Muehlenkamp et al, 2012; Vansteelandt et al, 2013; Claes and Muehlenkamp, 2014; Kostro et al, 2014; Islam et al, 2015; Cucchi et al, 2016). Within this clinical population both maladaptive food intake and NSSI behaviors can be implemented as a maladaptive ER strategy that enables the individual to avoid, manage or lessen unpleasant emotions (Chapman et al, 2006; Andover and Morris, 2014; McKenzie and Gross, 2014).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Notably, similar ER difficulties have been postulated for EDs and NSSI behaviors; namely, both reveal difficulties in thinking, planning, or implementing adaptive coping strategies (Solano et al, 2005; Claes et al, 2010; Muehlenkamp et al, 2012; Vansteelandt et al, 2013; Claes and Muehlenkamp, 2014; Kostro et al, 2014; Islam et al, 2015; Cucchi et al, 2016). Within this clinical population both maladaptive food intake and NSSI behaviors can be implemented as a maladaptive ER strategy that enables the individual to avoid, manage or lessen unpleasant emotions (Chapman et al, 2006; Andover and Morris, 2014; McKenzie and Gross, 2014).…”
Section: Introductionmentioning
confidence: 65%
“…Increasing evidence supports preceding emotion regulation (ER) models (Linehan, 1993; Gross, 1998) that postulate that ER difficulties often lead to the implementation of less appropriate strategies (e.g., maladaptive food intake or deliberate self-harm) to mollify unpleasant emotions. Likewise, deficits in ER observed among individuals suffering from EDs have been hypothesized to underlie the high prevalence of non-suicidal self-injury (NSSI) behaviors, which range from 21 to 59% in this clinical population (Kostro et al, 2014; Claes et al, 2015b; Islam et al, 2015; Cucchi et al, 2016). Still, among individuals with clinical EDs, those who engage in NSSI have higher dietary restrictions and higher rates of binging and/or purging symptomatology (Stein et al, 2004; Selby et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Eating disorders (EDs) and nonsuicidal self-injury (NSSI) are two maladaptive behaviors with substantial co-occurrence that represent significant mental and physical health concerns (Cucchi et al, 2016; Kostro et al, 2014). Among those with EDs, a recent meta-analysis reported a lifetime history of NSSI of 32.7% among those with bulimia nervosa (BN) and 27.3% among those with anorexia nervosa (AN) (Cucchi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among those with EDs, a recent meta-analysis reported a lifetime history of NSSI of 32.7% among those with bulimia nervosa (BN) and 27.3% among those with anorexia nervosa (AN) (Cucchi et al, 2016). Among those with NSSI, one study found 19.4% of participants with a history of NSSI also experience ED symptoms (Muehlenkamp et al, 2012), while another study found 29.9% of people being treated for NSSI engaged in binging, purging, or food restriction (Washburn et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is a high prevalence of suicide attempts in individuals with EDs, with lifetime prevalence estimates ranging from 3.0% to 40% [1821]. The majority of research indicates that both NSSI and suicide attempts are more prevalent in individuals who engage in purging behaviors [12, 20, 22], which are also associated with deficits in emotion regulation.…”
mentioning
confidence: 99%